HUBUNGAN PENGETAHUAN PASIEN TENTANG KEMOTERAPI DENGAN KECEMASAN DALAM MENJALANI TINDAKAN KEMOTERAPI DI RSUD PANEMBAHAN SENOPATI BANTUL - Teovilus, Bayu; Rukmi, Dwi Kartika; Istianah, Umi (Media Ilmu Kesehatan, 2015)
Background: Chemotherapy is the administration of anti-neoplastic drugs that can cause tumor regression and inhibit its metastasis. Chemotherapy has several effects, both physically and sychologically. One of the mo s t f r e q u e n t psychological effect of chemotherapy is anxiety. Patients with excessive anxiety l e v e l require assistance from the nurse with the adequate information. Objective: To determine the relationship between the knowledge level on chemotherapy and the anxiety level in carrying out chemotherapy at Panembahan Senopati Hospital Bantul. Method: This research was a descriptive study with cross-sectional design. The reserach used a purposive sampling technique which employed 49 respondents. Data were collected with a questionnaire. The data was analysed with Kendall's Tau test. Results: There was a relationship between the knowledge level on chemotherapy and anxiety level in p a t i e n t s w h o u n d e r w e n t chemotherapy at Panembahan Senopati Hospital Bantul. Kendall's Tau test resulted a significant level of 0.00 (p<0.05) with a correlation coefficient value of 0.605, which showed a strong relationship. Conclusion: There was a significant relationship between the knowledge level on chemotherapy and t h e anxiety level in patients who underwent chemotherapy at Panembahan Senopati Hospital Bantul. Keywords: Knowledge, Anxiety, Chemothera